The Issue of Compiling the “Historical Dictionary of the Kazakh Language” Based on Written Monuments (Eurasian Journal of Philology Science and Education, 2026)
To date, a comprehensive Historical Dictionary of the Kazakh Language has not yet been compiled, and the historical lexical corpus of the Kazakh language based on written monuments of the ancient, medieval, and modern Turkic periods has not been fully collected. Diachronic studies conducted by linguists contain abundant information and etymological analyses that reveal the development of the Kazakh language. However, this historical data has not been systematically organized or subjected to historical lexicographic analysis. It is well known that a Historical Dictionary can only be compiled by thoroughly collecting the historical lexicon from manuscripts and original texts and identifying semantic, phonetic, and morphological changes of each word. This article discusses the necessity of the Historical Dictionary and its significance in studying language development. First and foremost, it is necessary to select relevant sources, collect linguistic material, trace the semantic evolution of words across various written monuments, reflect phonetic and morphological shifts, and lexicographically systematize the entries. These tasks must be carried out in stages and based on historical data and linguistic analysis to ensure a high-quality dictionary. As early as the beginning of the 20th century, scholars emphasized that the Historical Dictionary reflects the national consciousness and ideology of an entire people. We cannot deny that such a dictionary contributes to the awakening of national identity. The main objective of the Historical Dictionary is to illustrate the diachronic development of the core historical vocabulary of the Kazakh language. It will comprehensively present lexemes from ancient periods that have been preserved in the modern language system, undergone semantic change, acquired new meanings, fallen out of use, or undergone stylistic transformations. Compiling such a dictionary with detailed linguistic-historical descriptions based on actual written monuments is one of the key objectives in contemporary Kazakh linguistics.Keywords: manuscript text, original text, historical dictionary, lexicographic research, etymological analysis.